Racial differences in primary sclerosing cholangitis mortality is associated with community socioeconomic status. (21st July 2021) - Are, Vijay S.; Vilar‐ Gomez, Eduardo; Gromski, Mark A.; Akisik, Fatih; Lammert, Craig; Ghabril, Marwan; Chalasani, Naga; Vuppalanchi, Raj; Nephew, Lauren D.
Abstract: Background and Aims: Natural history and outcomes data in PSC are mostly derived from cohorts where Blacks have been underrepresented. It is unknown if there are differences in mortality between Blacks and Whites with PSC. Methods: PSC patients seen at our institution from June 1988 to Jan 2019 were identified by merging prospective ERCP hepatology‐clinic databases and liver‐transplant registry. Data on race, clinical events, and death was obtained through chart review. Data on community health were collected using indices from county health rankings. Cumulative incidence of death was calculated using liver transplant (LT) as a competing risk. Results: Of 449 patients, 404 were White and 45 were Black. The median‐duration of follow‐up was 7 years (IQR:3, 13). Black patients were younger at presentation than White patients (36.3 vs 42.5 years., P  = .013). Disease severity as indicated by Mayo Risk Score categories (low 27% vs 31%, intermediate 54% vs 49% and high 19% vs 19%, P  = .690), comorbidity burden and frequency of cirrhosis (42% vs 35%, P  = .411) were similar between Blacks and Whites. Cumulative incidence of liver‐related death, with LT as a competing risk was significantly higher in Blacks compared to Whites (sHR 1.80, 95%CI 1.25, 2.61, P  = .002). There was a significant interaction between race and community socioeconomic factors that attenuated the racial difference in mortality (sHR 1.01, 95%CI 0.99, 1.04, P  = .345). Conclusions: Blacks with PSC present at a younger age with a similar disease severity as Whites but have higher liver related mortality that is mediated in part through community health.